1997
DOI: 10.7326/0003-4819-127-4-199708150-00006
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Plasma Concentrations of Antituberculosis Drugs in Patients with HIV Infection

Abstract: Reduced total drug exposure may be related to malabsorption in persons with HIV infection or AIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
111
1
7

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(123 citation statements)
references
References 0 publications
4
111
1
7
Order By: Relevance
“…However, this study demonstrated that the bioavailability of RMP in HIV-infected patients with and without TB was decreased, as evidenced by a significant reduction in peak concentration and exposure. Similar findings have been reported by Sahai et al (17), who conducted a pharmacokinetic study of Canadian subjects with HIV infection. Low concentrations of RMP in blood could be due to malabsorption of the drug (2).…”
supporting
confidence: 77%
See 1 more Smart Citation
“…However, this study demonstrated that the bioavailability of RMP in HIV-infected patients with and without TB was decreased, as evidenced by a significant reduction in peak concentration and exposure. Similar findings have been reported by Sahai et al (17), who conducted a pharmacokinetic study of Canadian subjects with HIV infection. Low concentrations of RMP in blood could be due to malabsorption of the drug (2).…”
supporting
confidence: 77%
“…However, patients with advanced human immunodeficiency virus (HIV) disease with or without diarrhea may not adequately absorb anti-TB drugs (3,(13)(14)(15). Also, the degrees of malabsorption appear to differ across populations (4,6,17,19). We recently observed that HIV-infected patients with and without TB had malabsorption of rifampin (RMP) and isoniazid (INH), as determined on the basis of the urinary excretion of the drugs (7).…”
mentioning
confidence: 99%
“…For humans without tuberculosis who received a single 250-mg oral dose of isoniazid, elimination half-lives have been reported to be 1.2 and 3.3 h in fast and slow acetylators, respectively, and peak concentrations in plasma (at 1 h postdosing) have been reported to be 2.44 and 3.64 g/ml, respectively (25). Several investigators in the United States have reported that the absorption of antimycobacterial agents is impaired in patients with AIDS (18,27,29 . However, this effect was not demonstrated in Kenyan patients, in whom concentrations in plasma were not different among individuals with or without AIDS or with or without diarrhea (9).…”
mentioning
confidence: 99%
“…The extent of reduction of serum carotene is secondary to its oxidation and consequent depletion by singlet oxygen (Bendich, 1993). Circulating concentrations of drugs can also be lower in the HIV-infected than in the HIV-uninfected (Sahai et al, 1997). We chose treatment with a relatively high dose of natural mixed carotenoids in the current trial because of the known absorption defect in AIDS that affects drug and micronutrient concentrations, and because similar doses of carotenoids are safe in short-and long-term use.…”
Section: Mixed Carotenoids In Hiv Infectionmentioning
confidence: 99%